Moral Messages in the Film Wedding Agreement The Series (Roland Barthes Semiotic Analysis) - Chairun Nisa, Salsa Nabilla; Deni, Indira Fatra (International Journal of Cultural and Social Science, 2023)
Film is a medium that is used and developed by humans to convey communication through storylines and narratives in the form of audio and visual. In the world of cinema, films have their own value. Film as an object of art should be judged artistically, not rationally. Semiotics is the study of science or analytical methods to examine signs in a context. Therefore, a good film will convey information well as well. Implicit messages in a film are the ideas, ideas, and goals of the director or film script writer.